Beyond appetite regulation: Targeting energy expenditure, fat oxidation, and lean mass preservation for sustainable weight loss. Issue 4 (25th March 2022) - Christoffersen, Berit Østergaard; Sanchez‐Delgado, Guillermo; John, Linu Mary; Ryan, Donna H.; Raun, Kirsten; Ravussin, Eric
Abstract: New appetite‐regulating antiobesity treatments such as semaglutide and agents under investigation such as tirzepatide show promise in achieving weight loss of 15% or more. Energy expenditure, fat oxidation, and lean mass preservation are important determinants of weight loss and weight‐loss maintenance beyond appetite regulation. This review discusses prior failures in clinical development of weight‐loss drugs targeting energy expenditure and explores novel strategies for targeting energy expenditure: mitochondrial proton leak, uncoupling, dynamics, and biogenesis; futile calcium and substrate cycling; leptin for weight maintenance; increased sympathetic nervous system activity; and browning of white fat. Relevant targets for preserving lean mass are also reviewed: growth hormone, activin type II receptor inhibition, and urocortin 2 and 3. We endorse moderate modulation of energy expenditure and preservation of lean mass in combination with efficient appetite reduction as a means of obtaining a significant, safe, and long‐lasting weight loss. Furthermore, we suggest that the regulatory guidelines should be revisited to focus more on the quality of weight loss and its maintenance rather than the absolute weight loss. Commitment to this research focus both from a scientific and from a regulatory point of view could signal the beginning of the next era in obesity therapies.